Analisis Nilai Kejujuran Dalam Cerita Pendek Pelangi Di Warung Kakek Karya Tiflatul Husna : Sebuah Kajian Reader Response (Lembaga Pengembangan Kinerja Dosen, 2025)
This study investigates elementary-school readers’ constructions of honesty in Tiflatul Husna’s children’s short story “Rainbow at Grandfather’s Shop” through the lens of experimental reader-response theory. It aims to chart how young readers interpret the honesty embodied by Bang Muslim and to examine the mediating effects of socio-cultural background and personal experience on that reception. A qualitative, descriptive-interpretative design was adopted. Data were gathered from textual analysis, closed- and open-ended questionnaires administered to forty pupils at SDIT Mutiara Cendekia, and follow-up interviews, all triangulated across sources. Employing Miles and Huberman’s analytic cycle (data reduction, display, verification), three dominant categories emerged: honesty as sincere assistance, verbal truthfulness, and integrity regarding property. Findings show that 57.5 % of respondents construed Bang Muslim’s honesty primarily as altruistic help, 30 % stressed fidelity to facts, and 12.5 % equated honesty with refraining from taking what is not one’s own. Interpretative variation was conditioned by cultural habitus (Javanese, Malay, Minangkabau, Palembang) and prior exposure to character education. Honesty is thus perceived performatively, as concrete action, rather than as abstract moral diction, underscoring children’s fiction as a potent vehicle for character formation. The study extends reader-response scholarship by presenting a concrete child-reader model and informs curriculum design for Indonesia’s Character Education Strengthening programme. Future work should employ cross-regional comparisons and classroom action research to test the transferability of these insights.